THE SOCIO-ECONOMIC RIGHTS OF CHILDREN WITH DISABILITIES IN SOUTH AFRICA: A COMPARISON BETWEEN THE AFRICAN CHARTER ON THE RIGHTS AND WELFARE OF THE CHILD AND THE CONVENTION ON THE RIGHTS OF PERSONS WITH DISABILITES (African Disability Rights Yearbook, 2021)
International law plays an important role in the promotion and protection of the socio-economic rights of children with disabilities. International law bolsters the mechanisms used to keep states accountable in the fulfilment of their obligations. This article discusses two international law instruments, namely, the African Charter on the Rights and Welfare of the Child and the Convention on the Rights of Persons with Disabilities, with the aim to examine how they provide for and protect the socio-economic rights of children with disabilities in the South African context and, by implication, children in the African context as a whole. Socioeconomic rights place a duty on states to ensure that all people have access to the basic necessities of life, which include education, health care, food and water. Access to these and other services ensures that children with disabilities, like all other children, grow and develop in a manner that is cognisant of their specific needs and best interests. The discussion takes the form of a focused comparison of the two instruments, through which similarities and differences will be highlighted. The discussion further points out the different ways in which these instruments could reinforce the protection provided in national law to ensure that the socio-economic rights of children with disabilities in South Africa are protected and promoted.